Between Technological Advancement and Protectionism: The Bumpy Evolution from MP3 Players to Smartphones in Korea - Parc, Jimmyn (Archīum Ateneo, 2024)
In recent years, K-pop or Korean popular songs have enjoyed immense popularity around the world. However, the situation was very different before the mid-2000s when the industry was suffering from widespread piracy of its music. Furthermore, the emergence of the MP3 phone in the early 2000s provoked two critical conflicts. One was between the producers of the MP3 phone who were large conglomerates and the manufacturers of the standalone MP3 player who were smaller companies that feared for their future. The other conflict was between the producers of the MP3 phone and the Korean music industry who believed this new device would hinder their development. Given the current global popularity of K-pop, it is meaningful to analyze the position and rationale of these players at the time and their consequences. In brief, protecting existing industries hindered the corporate and industrial adaptions in the global competition and held back the momentum to explore innovation and a new business model. First, the MP3 player manufacturers encountered serious financial and managerial problems and even went into bankruptcy because they were too slow in pursuing change. Second, the Korean conglomerates were late in producing a new digital device, the smartphone, and entering its growing market. Third, the Korean music industry was able to survive but only because entertainment companies have adopted a new business model that generated alternative sources of earnings. This paper demonstrates the importance of having a broader view and recognition of industrial dynamics in formulating effective policies.